Wave propagation in pressurised composite structures with frequency band gap behaviour - Ampatzidis, Theofanis; Chronopoulos, Dimitrios (2016)
In engineering there are numerous examples of structures, such as train rails and airplane fuselages, that present periodicity in their geometry or mechanical properties. It has been observed that this periodicity leads to banded frequency response after excitation. These band gaps can be engineered to isolate noise and vibrations of the periodic structure. In this paper an infinite composite sandwich beam with hollow and pressurised core cells as periodic band gap inducing factors was examined. Wave finite element (WFE) method was used to predict the effect of pressured core cells periodicity on wave propagation and band gaps generation. Three low order finite elements (FE) models were produced using commercially available FE software package. These models consisted of a small section of the simple sandwich beam with homogenous core, with hollow core and with pressurised hollow core.